2021
DOI: 10.1002/cbic.202000870
|View full text |Cite
|
Sign up to set email alerts
|

SP3‐FAIMS Chemoproteomics for High‐Coverage Profiling of the Human Cysteinome**

Abstract: Chemoproteomics has enabled the rapid and proteome-wide discovery of functional, redox-sensitive, and ligandable cysteine residues. Despite widespread adoption and considerable advances in both sample-preparation workflows and MS instrumentation, chemoproteomics experiments still typically only identify a small fraction of all cysteines encoded by the human genome. Here, we develop an optimized sample-preparation workflow that combines enhanced peptide labeling with singlepot, solid-phase-enhanced sample-prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
133
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(143 citation statements)
references
References 65 publications
(129 reference statements)
7
133
2
1
Order By: Relevance
“…In recent years the scope, scale, and speed with which chemically reactive amino acids can be profiled has accelerated dramatically; chemoselective probes are now available for cysteine 4 , serine 39 , lysine 5 , methionine 6 , tyrosine 7 , aspartate/glutamate 9,40 , tryptophan 41 , and histidine 42 . Supporting this, advances in mass-spectrometry have significantly expanded the number and rate at which individual reactive sites can be profiled 43,44 , and subsequently exploited by electrophilic drug hunters. CORe provides a technology bridge between unbiased proteomic profiling of reactive sites and protein sequence-function relationships, and will be a valuable tool for proteome engineers alongside other methods including MAGE, CRMAGE and CREATE.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years the scope, scale, and speed with which chemically reactive amino acids can be profiled has accelerated dramatically; chemoselective probes are now available for cysteine 4 , serine 39 , lysine 5 , methionine 6 , tyrosine 7 , aspartate/glutamate 9,40 , tryptophan 41 , and histidine 42 . Supporting this, advances in mass-spectrometry have significantly expanded the number and rate at which individual reactive sites can be profiled 43,44 , and subsequently exploited by electrophilic drug hunters. CORe provides a technology bridge between unbiased proteomic profiling of reactive sites and protein sequence-function relationships, and will be a valuable tool for proteome engineers alongside other methods including MAGE, CRMAGE and CREATE.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were prepared as reported. 15 Jurkat proteome (200 μL of 1 mg/mL) was first labeled with IAA 1 or other reagents (4 μL of 100 mM stock solution in DMSO, final concentration = 2 mM) for 1h at ambient temperature. CuAAC was performed with biotin-azide 2 or other reagents (4 μL of 200 mM stock in DMSO, final concentration = 4 mM), TCEP (4 μL of fresh 50 mM stock in water, final concentration = 1 mM), TBTA (12 μL of 1.7 mM stock in DMSO/t-butanol 1:4, final concentration = 100 μM), and CuSO4 (4 μL of 50 mM stock in water, final concentration = 1 mM) for 1h at ambient temperature.…”
Section: Methodsmentioning
confidence: 99%
“…13,14 However, a central challenge of these studies is that they still only sample a small fraction (2.4%) of all cysteines in the human proteome (estimated to comprise >260,000 residues). 15 Closing this gap requires the development of optimized chemoproteomic sample preparation and data analysis workflows. Supporting this premise, our recent work revealed that using a SP3 cleanup method combined with on-line sample fractionation could achieve 5.5-fold increased coverage compared to prior methods, with decreased instrument time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eine Erhöhung der Zahl quantifizierter Cysteinreste im Proteom haben Keriann Backus und ihre Gruppe erreicht. 3) Neben der kupferkatalysierten Klick-Chemie wurden bisher nur wenige bioorthogonale Reaktionen eingesetzt. Cao und Coautor:innen haben die Suzuki-Miyaura-Reaktion für positionsaufgelöste proteomweite Experimente genutzt.…”
Section: Positionsaufgelöste Chemo Proteomische Methodenunclassified